The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.3390/su5114614
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Transacademic Interface Managers in Transformational Sustainability Research and Education

Abstract: Working towards sustainable solutions requires involving professionals and stakeholders from all sectors of society into research and teaching. This often presents a challenge to scholars at universities, as they lack capacity and time needed for negotiating different agendas, languages, competencies, and cultures among faculty, students, and stakeholders. Management approaches and quality criteria have been developed to cope with this challenge, including concepts of boundary organizations, transdisciplinary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 45 publications
(104 reference statements)
2
39
0
Order By: Relevance
“…Such a coordinator would foster organizational learning across the network and maintain a network 'memory'-providing information, facilitate collaborative arrangements, do trouble shooting, if necessary, and evaluate success and failure of collaborative efforts. Considering the inter-and transdisciplinary nature of almost all empirical sustainability projects, such a coordinator might benefit from specific training on how to facilitate collaboration at several interfaces (e.g., between disciplines or between scientists and stakeholders) (Brundiers et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a coordinator would foster organizational learning across the network and maintain a network 'memory'-providing information, facilitate collaborative arrangements, do trouble shooting, if necessary, and evaluate success and failure of collaborative efforts. Considering the inter-and transdisciplinary nature of almost all empirical sustainability projects, such a coordinator might benefit from specific training on how to facilitate collaboration at several interfaces (e.g., between disciplines or between scientists and stakeholders) (Brundiers et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…It departs from sustainability science as outlined by (Kates et al 2001) that calls for descriptiveanalytical knowledge on origin, structure, and functioning of sustainability problems to advance understanding of resilience and vulnerability in social-ecological systems. In transformational sustainability science, actionable knowledge is generated on solutions that alleviate the symptoms or change the underlying causal structures of sustainability problems (Wiek et al 2012;Brundiers et al 2013). To achieve these objectives, universities are increasingly engaged in multistakeholder, transdisciplinary efforts to catalyze sustainability transformation Trencher et al 2014a).…”
Section: Introductionmentioning
confidence: 99%
“…Since EfS/ESD pedagogy focuses on students and their engagement with issues and interactions outside of the class-room, an individual teacher/academic may need support to implement the curriculum. The contribution of Brundiers Wiek and Kay [6] specifically considers the need for a "transacademic interface manager" to support those participatory education efforts that are frequently an identifying feature of sustainability education and research. Their article, they say "provides practical guidance to universities on how to organize these critical endeavors more effectively" [6] (p. 4614), and intriguingly suggests that the idea of these managers can "offer students an additional career perspective" [6] (p. 4614) For those considering the potential benefits of establishing a transacademic interface manager role, or developing curriculum to develop related capabilities in graduates, Brundiers, Wiek and Kay [6] provide a rich description of the role and its development.…”
mentioning
confidence: 99%
“…A second target for future research lies in the professionalization of both teachers and stakeholders, who also need support to be able to effectively work in universitycommunity partnerships (Brundiers et al, 2013). A focus group discussion on effective student-stakeholder support, held with 14 RLE teachers after the closure of the eight studied RLEs (February 2016), showed that teachers were mainly occupied with organisational aspects of school-stakeholder collaboration, and showed yet limited openness for the further development of actual student-stakeholder support.…”
Section: Future Researchmentioning
confidence: 99%
“…Guzmán-Valenzuela, 2015). However, studies contributing to this debate only pay oblique attention to what is required from teachers to perform in university-community collaborative practices (Brundiers et al, 2013;Stauffacher et al, 2006). Until the date, a systematic identification of roles and tasks that teachers fulfil in a university-community collaborative learning environment, and the competencies that teachers should master to carry out these tasks, has not been done.…”
Section: 1mentioning
confidence: 99%